Spacing hinterland water for Algiers city (Algeria) - Medjadj, Tarek; Setti, M'hammed; Feloussia, Lahcene (Tecnología y ciencias del agua, 2024)
Of all the kinds of relationship, the one that links man with water is considered as profound and serious in geographical surveys. Yet in the past, the greatest threat to agriculture was a major problem, the attention of people is now captured by water in cities. The increasing need of water in Algiers is due to the growth of population and urbanism. On the other hand, there is a rise in water needs per capita. This problem didn’t arise during the last decades, but today the situation is no longer the same. It’s a considerable challenge for the capital Algiers, especially for the next generations. Using a geo-history method, which consists in studying the evolution of hinterland water space in time, we will direct our research towards the exposure of the influences exerted by the increase of water needs in the zone of study. The finality of the work is to identify the water resources around the Algiers City and that arises from the spacing of evolution hinterland water. We will obtain valuable information about the extension, the distance of the hinterland water supplier from the city of Algiers. The expected result of this work is to determine the hinterland which can be counted on to supply the city of Algiers with drinking water in the medium and long term. Finally, we can think of hydraulic planning and development based on the principles of sustainable development. This with the aim of proposing solutions to current problems and ensuring the needs of future generations.